The art of laughter: comic procedures of the Clown - Fonseca, Francisco Cristiano Marques da; Bezerra, Diego Brito; Aguiar, Amidete Melo de (Ephemera: Revista do Programa de Pós-Graduação em Artes Cênicas da Universidade Federal de Ouro Preto, 2026)
The clown is a multifaceted figure that traverses different historical and cultural contexts, constantly updating itself according to social demands. Its essence, marked by fragility, error, and subversion, reveals a creative power that transforms vulnerability into scenic strength. More than provoking laughter, clowning exposes human contradictions and challenges established norms. By inhabiting the present with authenticity, the clown questions ideals of perfection and the cult of happiness. As Achcar (2016) points out, the clown reminds us that suffering can also be a transformative force, recovering joy as a vital energy. Thus, clowning affirms itself not only as an artistic language of comedy but also as a space of resistance and critical reflection on the human condition.